Kualitas Hadis tentang Keutamaan Menyempurnakan Wudhu' dalam Tinjauan Studi Takhrij Hadis - Hanifatul Akmila (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about perfecting ablution. This study uses a qualitative approach by applying descriptive analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about perfecting ablution in the history of Bukhari no. 136. The results and discussion of this study indicate that the status of quality hadith is shahih that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Bukhari no. It is relevant to be used to motivate Muslims to perform ablution perfectly and to know the validity of ablution.